2013
DOI: 10.1155/2013/481348
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Release Surgery and Venous Hypertension in Early Hemodialysis Patients without Amyloid Deposits

Abstract: Aim. Carpal tunnel syndrome (CTS) is one of the frequent problems of the patients who underwent hemodialysis (HD). The role of venous hypertension due to arteriovenous fistula (AVF) has not been clarified completely; therefore, we aimed to investigate the role of venous hypertension due to AVF in hemodialysis patients who had CTS. Patients and Methods. We included 12 patients who had been receiving HD treatment for less than 8 years and the newly diagnosed CTS patients with the same arm of AVF. All patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…25 Warren also found that venous pressures were significantly raised before HD, 27 while Kocyigit found that venous pressure was significantly reduced following CTS decompression. 23 Moreover in the latter study, amyloid deposition as stained by Congo red was absent in all of their patients biopsy specimens. 23 Both of these studies point towards venous hypertension as a possible aetiological factor in CTS pathogenesis, however, do not elucidate on underlying mechanism for reduction in venous pressure post treatment.…”
Section: Aetiologymentioning
confidence: 57%
See 3 more Smart Citations
“…25 Warren also found that venous pressures were significantly raised before HD, 27 while Kocyigit found that venous pressure was significantly reduced following CTS decompression. 23 Moreover in the latter study, amyloid deposition as stained by Congo red was absent in all of their patients biopsy specimens. 23 Both of these studies point towards venous hypertension as a possible aetiological factor in CTS pathogenesis, however, do not elucidate on underlying mechanism for reduction in venous pressure post treatment.…”
Section: Aetiologymentioning
confidence: 57%
“…23 Moreover in the latter study, amyloid deposition as stained by Congo red was absent in all of their patients biopsy specimens. 23 Both of these studies point towards venous hypertension as a possible aetiological factor in CTS pathogenesis, however, do not elucidate on underlying mechanism for reduction in venous pressure post treatment. β2-microglobulin amyloid deposits are another proposed aetiological factor in CTS with AVF and was found in all biopsied samples after surgical decompression in 1 study of 21 patients.…”
Section: Aetiologymentioning
confidence: 57%
See 2 more Smart Citations
“…CTS affects 30-50% patients who have been on hemodialysis for over 10 years and over 80% patients who have been on hemodialysis for over 30 years. Specific factors contribute to the development of carpal tunnel syndrome in patients on chronic hemodialysis, including b2-microglobulin (b2-M) fiber deposits and arteriovenous (AV) fistula [5][6][7][8]. Malnutrition-inflammation-atherosclerosis syndrome is a common cause of increased mortality in chronic kidney disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%